Application of the MMGO Model at “Red Mujer” Corporation Usme-Bogotá 2020: A Case Study - Vargas Guzman, Wilson Camilo; Briceño Neuque, Ángela Patricia; Gomez Ardila, Janeth Liliana (Cooperativismo & Desarrollo, 2021)
The number of studies around the social economy has increased lately. This kind of studies includes broad fields of social analysis, including cooperativism, which try to consolidate collaborative work between institutions and, at the same time, favour society in general. Considering a research proposal, carried out by Universidad Minuto de Dios, we would like to know the actual market position of social organizations. After selecting a model that better fits these specific companies (we chose Model of Modernization for Organizational management (MMGO, for its Spanish initials), proposed by Universidad EAN), we decided to analyze an association that was actively contributing to the social economy, that is, the Corporación de Mujeres Campesinas "Red Mujer", which supports peasant women in the town of Usme. Once implemented the MMGO, we could know the business conditions and the market opportunities of the Corporation. At the same time, we could describe and analyze 16 strategic components. In this article, we analyze the results and describe the recommendations submitted to the “Red Mujer” to adapt rapidly in a highly competitive market, never losing sight of its original mission: support rural women.